1992
DOI: 10.1210/mend.6.2.1569966
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of sites mediating estrogen regulation of the rat creatine kinase B gene.

Abstract: We have previously confirmed the estrogen-induced protein of rat uterus to be creatine kinase B (CKB), and demonstrated a 1.7-kilobase pair fragment encompassing the promoter and adjoining 5'-flank to be capable of conferring estrogen responsiveness in HeLa cells. In this study we find an element at -550, aGGTCAgaaCACCCt, with limited similarity to the estrogen response element consensus, to be involved in conferring estrogen responsiveness on the CKB promoter. This element can bind estrogen receptor (ER) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 25 publications
2
30
1
Order By: Relevance
“…Results of previous studies suggest that formation of ERSp1 complexes regulates E2-induced transactivation of the cmyc, creatine kinase B, and cathepsin D genes (18,41,84). An ER-Sp1 complex, GGGCGGn 23 ACGGG, was previously identified (Ϫ199 to Ϫ165) in the cathepsin D promoter (41), and further analysis of this sequence has identified an XRE, namely FIG.…”
Section: Discussionmentioning
confidence: 96%
“…Results of previous studies suggest that formation of ERSp1 complexes regulates E2-induced transactivation of the cmyc, creatine kinase B, and cathepsin D genes (18,41,84). An ER-Sp1 complex, GGGCGGn 23 ACGGG, was previously identified (Ϫ199 to Ϫ165) in the cathepsin D promoter (41), and further analysis of this sequence has identified an XRE, namely FIG.…”
Section: Discussionmentioning
confidence: 96%
“…This finding acquired relevance when we became aware of how the functional synergism between Sp1 and ER , through the formation of the ER /Sp1 complex, was responsible of the activation of other E 2 -responsive genes. For instance, in the promoter region of such genes the half palindromic ERE sequence and Sp1 were separated by a number of nucleotides ranging from 10 to 23 nt, such as cyclin D1, bcl2, retinoic acid receptor 1, IGF-binding protein 4, adenosine deaminase, DNA polymerase , c-fos, cathepsin D, transcription factor-E2F1, creatine kinase B, human progesterone receptor A promoter and, recently, cad gene (Dubik & Shiu 1992, Wu-Peng et al 1992, Krishnan et al 1994, Rishi et al 1995, Porter et al 1996, Scholz et al 1998, Wang et al 1998, Petz & Nardulli 2000, Salvatori et al 2000, Saville et al 2000, Tanaka et al 2000, Vyhlidal et al 2000, Li et al 2001, Khan et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Both electrophoretic mobility shift assay (EMSA) and chromatin immunoprecipitation (ChIP) assay confirmed that the above-mentioned sequence is functionally involved in mediating the up-regulatory effect induced by E 2 on IRS-1 expression. The effect, as documented for other E 2 -responsive genes, occurs through the interaction between ER and Sp1 proteins, bound separately to the ERE half sequence and Sp1 responsive element respectively and present in the ERE/Sp1 region of the IRS-1 promoter (Dubik & Shiu 1992, Wu-Peng et al 1992, Krishnan et al 1994, Rishi et al 1995, Porter et al 1996, Scholz et al 1998, Petz & Nardulli 2000, Saville et al 2000, Khan et al 2003.…”
Section: Introductionmentioning
confidence: 97%
“…However, among them, only a small number have been shown to possess functional EREs within the transcription regulatory region. In mammals, these genes include transcription factors, such as JUN [32] , FOS [33] , PGR [34] , and TP53 [35] , intracellular signaling molecules, such as HRAS [36] , BCL2 [37] , and BRCA1 [38] , enzymes, such as CHAT [39] , NQO1 [40] , and CKB [41] , secreted proteins, such as LTF [42] , SCGB1A1 [43] , OVGP1 [44] , C3 [45] , and AGT [46] , hormones, such as LHB [47] , OXT [48] , PRL [49] , and AVP [50] , membrane proteins, such as SNAT2 [51] and VEGFA [52] , the motogen TFF1 [53] , and the protease CTSD [54] . These genes are assumed to directly mediate various estrogen actions in normal tissues, as well as in cancer and other diseases.…”
Section: Steroid Hormone Target Genes and The Transcription Cascadementioning
confidence: 99%